Stellar stargazer! - O'Connor, Jane.; Preiss-Glasser, Robin (New York : Harper, 2011)
Fancy Nancy and her father love stargazing, and during her first campout under the stars she describes the heavens to him and her sister, JoJo, using her fancy words.
1.8
K-3
Keywords: Fancy Nancy (Fictitious character) -- Juvenile fiction; Stars -- Juvenile fiction; Camping -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Sisters -- Juvenile fiction; Vocabulary -- Juvenile fiction; Fancy Nancy (Fictitious character) -- Fiction; Stars -- Fiction; Camping -- Fiction; Fathers and daughters -- Fiction; Sisters -- Fiction; Vocabulary -- Fiction; Fancy Nancy (Fictional character) -- Fiction; Stars -- Fiction; Camping -- Fiction; Father-daughter relationship -- Fiction; Sisters -- Fiction; Vocabulary -- Fiction; Picture books for children